New Horizons for High-Performance Computing. - Ang, James A.; Mountain, David J.; Williams, Joseph (Computer (00189162), 2022)
The authors describe an open innovation model that can be an organizing principle for future computing research, explain how high-performance computing as a lead user can guide public–private partnerships, and address workforce development.